IMPLEMENTASI DIGITALISASI PELAYANAN PUBLIK DAN KOMPETENSI SDM TERHADAP KEPUASAN MASYARAKAT PADA KANTOR KECAMATAN JATINANGOR KABUPATEN SUMEDANG - Putri, Mia Cahyani; Yuliyana, Wulan (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2023)
Jatinangor is one of the sub-districts in Sumedang Regency, West Java Province. The Janitangor District Office has 18 service products to serve the community, including making Family Cards and E-KTP. Administratively, Jatinangor District is divided into 12 villages, 137 RW and 515 RT with an area of ​​26.20 Km² (26.200 Ha). Thisiistudyiiaimsiito determine theiieffectiiofiithe variable digitization of public services and human resource competence on community satisfaction at the Jatinangor District office. The sampling technique used is probability sampling with a simple random sampling approach with a total of 100 respondents. The data obtained were analyzed using SPSS version 20 and data analysis techniques using descriptive and verification methods. The results of the study indicate that the digitization of public services and the competence of human resources both have a positive and significant influence on people's satisfaction. Simultaneously the digitization of public services and human resource competencies have a significant effect on people's satisfaction.